2019
DOI: 10.2147/cmar.s186114
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preoperative aspartate aminotransferase-to-platelet-ratio index as a predictor of posthepatectomy liver failure for resectable hepatocellular carcinoma</p>

Abstract: Purpose This study aimed to investigate the efficacy of preoperative aspartate aminotransferase-to-platelet-ratio index (APRI) score to predict the risk of posthepatectomy liver failure (PHLF) in patients with hepatocellular carcinoma (HCC) after liver resection, and to compare the discriminatory performance of the APRI with the Child–Pugh score, model for end-stage liver disease (MELD) score, and albumin–bilirubin (ALBI) score. Patients and methods A total of 1,044 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 37 publications
5
33
0
Order By: Relevance
“…Mai et al recently evaluated 1,044 hepatocellular carcinoma patients that underwent liver resection, and demonstrated that APRI could significantly predict post-hepatectomy outcomes (AUC = 0.743), in agreement with our results. This confirms the ability of the APRI to predict mortality after EH 27 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Mai et al recently evaluated 1,044 hepatocellular carcinoma patients that underwent liver resection, and demonstrated that APRI could significantly predict post-hepatectomy outcomes (AUC = 0.743), in agreement with our results. This confirms the ability of the APRI to predict mortality after EH 27 .…”
Section: Discussionsupporting
confidence: 79%
“…The APRI was introduced by Wai et al in 2003 as a predictive measure for fibrosis and cirrhosis in patients with chronic hepatitis 25 . Later, different studies concluded that its preoperative measures significantly predict post-hepatectomy morbidity and mortality [26][27][28] . Mai et al recently evaluated 1,044 hepatocellular carcinoma patients that underwent liver resection, and demonstrated that APRI could significantly predict post-hepatectomy outcomes (AUC = 0.743), in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver resection was performed when the preoperative imaging ndings indicated that all tumors could be resected within the hepatic functional reserve. Detailed and indications for liver resection were illustrated in our previous study [26].…”
Section: Surgical Procedures and Follow-upmentioning
confidence: 99%
“…Nonetheless, further research is necessary as few studies have been done evaluating use of PALBI for predicting PHLF. APRI is noninvasive and reliable for evaluating liver fibrosis and cirrhosis, [ 21 , 22 ] meanwhile a high preoperative APRI score have a high risk of PHLF in HCC patients [ 23 ]. However, APRI only includes two quantitative variables and has no ceiling effect.…”
Section: Introductionmentioning
confidence: 99%